2017
DOI: 10.1097/qai.0000000000001346
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Structured Mentor Mother Programs on 6-Month Postpartum Retention and Viral Suppression among HIV-Positive Women in Rural Nigeria: A Prospective Paired Cohort Study

Abstract: Structured PS significantly improved postpartum PMTCT retention and viral suppression rates among women in rural Nigeria. Introduction of structure can enhance the impact of PS interventions on PMTCT outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 18 publications
2
61
0
Order By: Relevance
“…7 This difference was present despite control sites also offering some individual peer support through local women living with HIV who were contracted, through the routine services, to provide similar help and counseling. The difference in effect appeared because of the quality of training and regular supervision provided to the expert mentor mothers and was not related to the ratio of women to local peer supporter or expert mentor mother.…”
Section: Peer Support Interventions and Retention In Care And Other Hmentioning
confidence: 99%
“…7 This difference was present despite control sites also offering some individual peer support through local women living with HIV who were contracted, through the routine services, to provide similar help and counseling. The difference in effect appeared because of the quality of training and regular supervision provided to the expert mentor mothers and was not related to the ratio of women to local peer supporter or expert mentor mother.…”
Section: Peer Support Interventions and Retention In Care And Other Hmentioning
confidence: 99%
“…Our study showed no signi cant association between the MoMent study's structured mentor mother support intervention and infant survival. While there is ample evidence on the positive impact of maternal peer support on maternal PMTCT retention, adherence and viral suppression, EID timeliness/uptake, and rate of vertical transmission in Nigeria (20,21) and in sub-Saharan Africa and globally (56)(57)(58)(59)(60)(61)(62), few studies explicitly report on its direct impact on HEI mortality. This may be due largely to sample size constraints; studies conducted so far-including ours-may not have been powered enough to investigate this.…”
Section: Discussionmentioning
confidence: 99%
“…Data presented in this paper was collected as part of the MoMent (Mother Mentor) study, one of six WHOsupported studies under its INSPIRE (Integrating and Scaling Up PMTCT through Implementation Research) initiative (18). MoMent evaluated the impact of structured maternal peer support on presentation/uptake for early infant diagnosis (EID) and maternal retention in care among women living with HIV and their HEI (19)(20)(21).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations